Physical training improves physical activity levels but is associated with amplification of sedentary behavior in older women - de Oliveira, Guilherme Lima; Sobrinho, Andressa C. S.; Benjamim, Cicero Jonas R.; da Silva Rodrigues, Guilherme; Rodrigues, Karine Pereira; Fernandes, Carlos Henrique; Corrêa, Adriano Bruno; Felicio, Tamara Nascimento; de Oliveira Gomes, Grace Angelica; Júnior, Carlos Roberto Bueno (Frontiers in Public Health, 2023)
Physical activity level (PAL) and sedentary behavior (SB) are independent predictors of mortality. It is unclear how these predictors interact with each other and health variables. Investigate the bidirectional relationship between PAL and SB, and their impact and health variables of women aged 60 to 70 years. One hundred forty-two older adults women (66.3 ± 2.9 years) considered insufficiently active were submitted to 14 weeks of multicomponent training (MT), multicomponent training with flexibility (TMF), or the control group (CG). PAL variables were analyzed by accelerometry and QBMI questionnaire, physical activity (PA) light, moderate, vigorous and CS by accelerometry, 6 min walk (CAM), SBP, BMI, LDL, HDL, uric acid, triglycerides, glucose and cholesterol total. In linear regressions, CS was associated with glucose (B:12.80; CI:9.31/20.50; p < 0.001; R2:0.45), light PA (B:3.10; CI:2, 41/4.76; p < 0.001; R2:0.57), NAF by accelerometer (B:8.21; CI:6.74/10.02; p < 0.001; R2:0.62), vigorous PA (B:794.03; CI:682.11/908.2; p < 0.001; R2:0.70), LDL (B:13.28; CI:7.45/16.75; p < 0.002; R2:0.71) and 6 min walk (B:3.39; CI:2.96/8.75; p < 0.004; R2:0.73). NAF was associated with mild PA (B:0.246; CI:0.130/0.275; p < 0.001; R2:0.624), moderate PA (B:0.763; CI:0.567/0.924; p < 0.001; R2:0.745), glucose (B:−0.437; CI:−0.789/−0.124; p < 0.001; R2:0.782), CAM (B:2.223; CI:1.872/4.985; p < 0.002; R2:0.989) and CS (B:0.253; CI: 0.189/0.512; p < 0.001; R2:1.94). The NAF can enhance CS. Build a new look at how these variables are independent but dependent simultaneously, being able to influence the quality of health when this dependence is denied.